2022
DOI: 10.3390/atmos13111766
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PM2.5 Monitoring in a Diesel Generator Workshop Using Low-Cost Sensors

Abstract: Particulates from diesel generator operation are a known air pollutant with adverse health effects. In this study, we used low-cost particulate matter (PM) sensors to monitor PM2.5 in a diesel generator plant. We compared the measurement results from a PM sensor and a reference instrument (DustTrak), and we found a high correlation between them. The data overestimation or underestimation of PM sensors implied the need for data calibration. Hence, we proposed a data calibration algorithm based on a nonlinear su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Calibrating these sensors can dramatically improve their accuracy. For instance, Feng et al (2022) reported a noticeable post-calibration improvement in R^2 from a range of 0.64-0.71 to 0.75-0.81 (Feng et al, 2022). Another study using a network of 19 sensors deployed over a period of 2 months in Sacramento, CA also observed a boost in post-calibration R^2 values from 0.6 to 0.73 (Mukherjee et al, 2019).…”
Section: The Importance Of Calibrationmentioning
confidence: 97%
“…Calibrating these sensors can dramatically improve their accuracy. For instance, Feng et al (2022) reported a noticeable post-calibration improvement in R^2 from a range of 0.64-0.71 to 0.75-0.81 (Feng et al, 2022). Another study using a network of 19 sensors deployed over a period of 2 months in Sacramento, CA also observed a boost in post-calibration R^2 values from 0.6 to 0.73 (Mukherjee et al, 2019).…”
Section: The Importance Of Calibrationmentioning
confidence: 97%